A New Computed Tomography Method to Identify Meningitis-Related Cochlear Ossification and Fibrosis before Cochlear Implantation. (April 2014) - Ichikawa, Kazunori; Kashio, Akinori; Mori, Harushi; Ochi, Atushi; Karino, Shotaro; Sakamoto, Takashi; Kakigi, Akinobu; Yamasoba, Tatsuya
Objective: To develop a new method to determine the presence of intracochlear ossification and/or fibrosis in cochlear implantation candidates with bilateral profound deafness following meningitis. Study Design: Diagnostic test assessment. Setting: A university hospital. Subjects and Methods: This study involved 15 ears from 13 patients with profound deafness following meningitis who underwent cochlear implantation. These ears showed normal structures, soft tissue, partial bony occlusion, and complete bony occlusion in 4, 3, 2, and 6 ears, respectively. We measured radiodensity in Hounsfield units (HU) using 0.5-mm-thick axial high-resolution computed tomography image slices at 3 different levels in the basal turn, the fenestration, and inferior and ascending segment sites, located along the electrode-insertion path. Pixel-level analysis on the DICOM viewer yielded actual computed tomography values of intracochlear soft tissues by eliminating the partial volume effect. The values were compared with the intraoperative findings. Results: Values for ossification (n = 12) ranged from +547 HU to +1137 HU; for fibrosis (n = 11), from +154 HU to +574 HU; and for fluid (n = 22), from −49 HU to +255 HU. From these values, we developed 2 presets of window width (WW) and window level (WL): (1) WW: 1800, WL: 1100 (200 HU to 2000 HU) and (2) WW: 1500, WL: 1250 (500 HU to 2000 HU). The results using these 2 presets corresponded well to the intraoperative findings. Conclusion: Our new method is easy and feasible for preoperative determination of the presence of cochlear ossification and/or fibrosis that develops following meningitis.